2018
DOI: 10.1080/01902148.2018.1473530
|View full text |Cite
|
Sign up to set email alerts
|

The effect of captopril on lipopolysaccharide-induced lung inflammation

Abstract: The results of this study showed that captopril dose-dependently reduced total and differential WBC counts, while it improved serum oxidant/antioxidant biomarkers and histopathological changes in LPS-treated rats. These results indicate a therapeutic potential for captopril on systemic inflammation and oxidative stress against LPS-induced lung injuries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 37 publications
3
5
0
Order By: Relevance
“…Furthermore, LPS decreased the IL-4 level but increased IFN-c, TGF-β1, and PGE2 levels in the BALF. Moreover, pathological insults of the lung such as lung inflammation, epithelial damage, emphysema, and fibrosis confirmed LPSinduced lung injury in the current study which was also shown in the previous studies [8,10].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, LPS decreased the IL-4 level but increased IFN-c, TGF-β1, and PGE2 levels in the BALF. Moreover, pathological insults of the lung such as lung inflammation, epithelial damage, emphysema, and fibrosis confirmed LPSinduced lung injury in the current study which was also shown in the previous studies [8,10].…”
Section: Discussionsupporting
confidence: 91%
“…In the LPS-administered animals, decreased lymphocytes percentage was due to increased total WBC count. In fact, increased absolute lymphocytes count was demonstrated in previous studies [8,10].…”
Section: Discussionsupporting
confidence: 50%
See 2 more Smart Citations
“…Reactive oxygen species (ROS) play a pivotal role in inflammation ( 16 ). Under normal condition, ROS are neutralized by antioxidants so as to maintain the balance of the oxidant and antioxidant system; under pathologic conditions, the level of ROS is expected to be increased and the activity of the antioxidant system decreased, directly leading to an imbalance trending to oxidation, termed oxidative stress ( 17 , 18 ). As oxidative stress is an important process during the pathophysiology of inflammatory diseases, including pulmonary inflammation ( 19 ), the present study examined the levels of ROS and antioxidant-oxidant enzymes including MDA, LDH and SOD to verify the effect of UCF-101 on oxidative stress.…”
Section: Discussionmentioning
confidence: 99%